Effect of Waste Plastic on the Strength Characteristics of the Subgrade for the Flexible Pavement - Jindal, Kartik (My University, 2014)
The Biggest challenge in a developing country like India is to build a full network of road system with limited financial source available. Use of local materials can considerably lower down the construction cost. If the stability of local soil is not adequate for supporting wheel loads, the properties are improved by soil stabilization techniques e.g. use of geogrids, using randomly distributed fiber, or waste plastic in the subgrade soil, this can help in improving strength of subgrade. Research has been done in this area to improve engineering performance of subgrade soil by adding different types of waste plastic content. In this study different types of waste plastic were randomly mixed with the soil, then a series of California Bearing Ratio (CBR) tests were conducted to evaluate the strength of subgrade soil. High density polyethylene (HDPE), Low density polyethylene (LDPE) and Polypropylene (PP) at various percentages were used for improving soil strength. Results from the CBR tests established that addition of these materials in subgrade soil gives efficient strength to subgrade soil. It was observed that the CBR value increases with increase in fiber content upto a certain percentage but decreases with further addition of waste plastic content. The pavement sections has been designed with the modified subgrade using HDPE, LDPE & PP and the critical strain values at the top of the subgrade and at the bottom of the bituminous layer has been analysed and compared with the allowable values as per IRC: 37-2012 for the traffic loading of 150 msa for the four lane divided state highway project. The reduction in the crust thickness and saving in the project cost has been compared for the different subgrade with different waste plastics and by varying plastic contents.
ME, CED
Keywords: California Bearing Ratio; Bearing Ratio Index; Waste Plastic; Pavement Design; CED